2020
DOI: 10.3233/jad-200109
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and Imaging Calcium Biomarkers of Aging in Male and Female 5×FAD Mice

Abstract: Background: In animal models and tissue preparations, calcium dyshomeostasis is a biomarker of aging and Alzheimer’s disease that is associated with synaptic dysfunction, neuritic pruning, and dysregulated cellular processes. It is unclear, however, whether the onset of calcium dysregulation precedes, is concurrent with, or is the product of pathological cellular events (e.g., oxidation, amyloid-β production, and neuroinflammation). Further, neuronal calcium dysregulation is not always present in animal models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 132 publications
(158 reference statements)
0
7
0
Order By: Relevance
“…Although a lack of acuity changes in 4-month-old 5xFAD mice has been reported, 83 85 visual contrast sensitivity per se has not been studied to our knowledge. This is important to address, because an early reduction in visual contrast sensitivity is also found in humans with AD.…”
Section: Discussionmentioning
confidence: 91%
“…Although a lack of acuity changes in 4-month-old 5xFAD mice has been reported, 83 85 visual contrast sensitivity per se has not been studied to our knowledge. This is important to address, because an early reduction in visual contrast sensitivity is also found in humans with AD.…”
Section: Discussionmentioning
confidence: 91%
“…Experiments were performed using age- and sex-matched littermates at the ages of 5 and 10–12 weeks. The Alzheimer’s disease 5xFAD female mice 67 at the age of 6 months and their WT littermates were gifts form Dr. Geoffrey Murphy. All mice were housed in a pathogen-free animal facility at 22 ± 1 °C on a 12-h light/dark cycle with 40–60% humidity and fed a low-fat diet (13% fat, 57% carbohydrate, and 30% protein, LabDiet 5LOD), unless otherwise indicated.…”
Section: Methodsmentioning
confidence: 99%
“…These mice harbour two humanized transgenes: (1) the amyloid‐β precursor protein gene with the Swedish, Florida and London mutations and (2) the presenilin‐1 ( PSEN1 ) gene harbouring the M146L and L286V mutations. It is important to note here that we 45 and others 46 have demonstrated that the neurological and behavioural phenotypes on the C57BL/6J genetic background are less severe and occur at later timepoints when compared to that observed on the original C57BL6/SJLF1 hybrid background 42 . Mice were randomly assigned to treatment groups for each experiment.…”
Section: Methodsmentioning
confidence: 99%